Respostas
respondido por:
4
y = -x² + 6x - 8
a = -1; b = 6; c = -8
Delta:
Δ = b² - 4ac
Δ = 6² - 4 * (-1) * (-8)
Δ = 36 - 32
Δ = 4
Bhaskara:
x = - b ± √Δ / 2a
x = - 6 ± √4 / 2 * (-1)
x = - 6 ± 2 / -2
x' = - 6 - 2 / -2 = -8 / -2 = 4
x'' = - 6 + 2 / -2 = -4 / -2 = 2
S = {2, 4}
Espero ter ajudado. Valeu!
a = -1; b = 6; c = -8
Delta:
Δ = b² - 4ac
Δ = 6² - 4 * (-1) * (-8)
Δ = 36 - 32
Δ = 4
Bhaskara:
x = - b ± √Δ / 2a
x = - 6 ± √4 / 2 * (-1)
x = - 6 ± 2 / -2
x' = - 6 - 2 / -2 = -8 / -2 = 4
x'' = - 6 + 2 / -2 = -4 / -2 = 2
S = {2, 4}
Espero ter ajudado. Valeu!
mryannh:
obgd
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás